2018
DOI: 10.1002/jcb.26782
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and pharmacological characterization of Trimersurus malabaricus snake venom

Abstract: Trimeresurus malabaricus is a venomous pit viper species endemic to southwestern part of India. In earlier reports, we have shown that envenomation by T. malabaricus venom leading to strong local tissue damage but the mechanism of action is not clearly revealed. Local tissue damage affected by T. malabaricus venom is of great importance since the poison has serious systemic effects including death in the case of multiple attacks. The present study details the major manifestations of T. malabaricus venom and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In addition, green pit vipers were responsible for 58% of snakebites reported in Vietnam in 2017 [9]. Trimeresurus venom varies in toxicity between species; prolonged clotting time is a significant symptom observed in humans [10], and tissue damage and hematotoxicity in bite victims have also been reported [11,12]. Since there is no species-specific antivenom available for Trimeresurus, except T. albolabris, the only treatment available for bite cases has been a hetero-specific antivenom [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, green pit vipers were responsible for 58% of snakebites reported in Vietnam in 2017 [9]. Trimeresurus venom varies in toxicity between species; prolonged clotting time is a significant symptom observed in humans [10], and tissue damage and hematotoxicity in bite victims have also been reported [11,12]. Since there is no species-specific antivenom available for Trimeresurus, except T. albolabris, the only treatment available for bite cases has been a hetero-specific antivenom [13].…”
Section: Introductionmentioning
confidence: 99%
“…As in our previous study [ 13 ], here we found a hyaluronidase in the venom of N. fodiens . This non-toxic protein is commonly present in many animal venoms, including venoms of snakes, spiders and ants [ 44 , 61 , 62 ], and acts as a toxin spreading factor [ 60 , 61 ]. Due to its ability to hydrolyze connective tissue, hyaluronidase facilitates the action of other venom components [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These components are linked to the toxic activities of these venoms, such as paralysis and convulsions, irregular respiration, inhibition of heart rate, increase in vascular permeability, decrease in blood pressure, haemolysis, and death [ 7 , 9 , 10 , 14 ]. Hyaluronidase commonly occurs in venoms of various animal taxa, but is devoid of toxic activity [ 16 , 17 ]. Instead, due to its ability to hydrolyse connective tissue, it promotes the spreading of toxins after envenomation [ 8 , 18 ].…”
Section: Introductionmentioning
confidence: 99%